PERAN KARAKTERISTIK PEKERJAAN, PEMBERDAYAAN DAN MOTIVASI TERHADAP KINERJA DOSEN MELALUI KOMITMEN ORGANISASIONAL (Studi pada AKPELNI SEMARANG) (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study aims to examine and analyze The role of job characteristics, empowerment and motivation on lecturer performance with organizational commitment as mediation on Akpelni Semarang. This study was conducted using population and carried on in Akpelni lecturer who has minimum term of 5 years. Engineering test data used in this study include validity, reliability testing, regression analysis, t test and mediation. The results of the analysis and discussion showed that the job characteristic positive and significant impact on Organizational Commitment, Empowerment and no significant negative effect on Organizational Commitment, Motivation positive and significant impact on Organizational Commitment, Job Characteristics and no positive effect was not significant for Lecturers Performance, Empowerment influential positive and significant for Lecturers Performance, Motivation no positive effect and no significant effect on performance and Lecturer of Organizational Commitment positive but not significant effect on performance Lecturer. The results showed that job characteristics does not affect performance directly Lecturer, Empowerment Lecturer directly affect performance and motivation are not directly influence the performance Lecturer. Keywords: Job Characteristics, Empowerment, Motivation, Organizational Commitment and Performance Lecturer